Vem curtir o embalo desse som: a trajetória de um artista-professor - LOPES, William Cezar Gonzaga (2022)
This monograph was developed through personal and community research, of a qualitative nature. It recounts memories of a hidden curriculum, where all the paths traveled by the author resulted in a summation for the progress of this work of completion. In it, excerpts from the artistic-personal and artistic-professional trajectory are reported, containing images to better understand, as well as a research on the brega and the brega paraense. For this reason, the work was entitled "Come and enjoy the sound of this sound: the trajectory of a artist-teacher".